Application of Topical Tranexamic Acid Reduces Postoperative Blood Loss after Posterior Spinal Fusion with Instrumentation in Patients with Adolescent Idiopathic Scoliosis - Jongkittanakul, Sarut; Tanaviriyachai, Terdpong; Choovongkomol, Kongtush; Piyapromdee, Urawit; Sudprasert, Weera (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: There is limited literature regarding the topical use of tranexamic acid (TXA) to control postoperative bleeding during spinal deformity correction and fusion procedures, which often require blood transfusions. This study aimed to evaluate the effect of topical TXA on postoperative blood loss in patients undergoing deformity correction and posterior spinal fusion (PSF) surgeries. Methods: A retrospective study was conducted between January 2011 and April 2017 in 51 patients with adolescent idiopathic scoliosis who underwent long-segment PSF with hybrid thoracic-hook pedicle screw instrumentation or pedicle-screw-alone constructs. Twenty-five patients were assigned to receive topical TXA (1 g/20 mL), and the drain was clamped for 2 h. Twenty-six patients in the control group were treated with antifibrinolytic agents. Results: Median drainage blood loss, median day of drain removal, and median postoperative hospitalization were significantly lower in the topical TXA group (all p <0.05). The postoperative packed red cell transfusion rate was significantly lower in the topical TXA group than that in the control group (15 of 25, 60% vs. 23 of 26, 88.5%; p=0.02; risk ratio, 0.68; 95% confidence interval, 0.48–0.96). Conclusions: The use of topically administered 1 g TXA in AIS patients undergoing instrumented PSF effectively reduced postoperative transfusion requirements, decreased the total amount of drainage blood loss, reduced the time till drain removal, and shortened the length of postoperative hospitalization.